The Orientalist Paradigm and Its Implications for Interreligious Dialogue in the Era of Globalization: Paradigma Orientalis dan Implikasinya bagi Dialog Antaragama di Era Globalisasi - Ichwayudi, Budi; Syabrowi, Syabrowi; Septiana, Fira; Zuhria, Fristika Maulida Aminatuz (Institut Agama Islam Negeri Kerinci, 2025)
Orientalist studies on Islam have played a significant role in shaping Western perceptions and understanding of the religion. Throughout the history of interaction between Islam and the Western world, Orientalist studies have served both as a bridge of knowledge and a field of controversy. As times have evolved, the challenges of pluralism and diversity demand an inclusive and equal platform of communication among religious adherents. This article explores in depth the implications of Orientalist studies on the dynamics of interreligious dialogue in the era of globalization, particularly between Islam and other major world religions. The focus of this article is to analyze both the positive contributions and negative impacts of Orientalist studies, as well as the integration of a moderate approach in responding to the legacy of Orientalism. This research employs a descriptive qualitative method with a literature review approach. The findings reveal that Muslim responses to Orientalist studies are divided into two: some reject them due to perceived hidden agendas, while others accept them with critical reservations as a means of internal reflection and correction. In this context, interreligious dialogue becomes a strategic space to correct misunderstandings and strengthen the values of justice, tolerance, and peace. Orientalist studies have both positive and negative effects on interreligious dialogue. On one hand, biases and misperceptions introduced by Orientalist studies may hinder dialogue and exacerbate prejudice. On the other hand, objective Orientalist studies in the globalized era can enrich interfaith knowledge and open up opportunities for deeper understanding among religious communities.